PENGARUH SIFAT KEPRIBADIAN LOCUS OF CONTROL DAN SELF-EFFICACY PADA PEMAHAMAN AKUNTANSI - Putra, I Gst. B Ngr. P.; Damayanti, Ni Nyoman Sri Rahayu; Lestari, Ni Luh Putu Ratna Wahyu; Pradnyanitasari, Putu Dian; Jayawarsa, A.A. Ketut (Jurnal Aplikasi Akuntansi, 2019)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselve, and society. Good competence is one aspect that can improve student learning outcomes. Student competency is not the same as those of other student.  Competency can be formed from outside or from within the individual itself. Family support, environment, and the condition of facilities and infrastructure is one factor that give a big impact to person’s competencies. A person's behavior will be characterized by the nature of his personality. Locus of control and self-efficacy are two traits that able to change a person's behavior into one action or effort to carry out the learning process. The respondents of this study were Accounting students of Warmadewa University which already passed the 7’th semester. Data were collected by questionnaire technique. This research used multiple linear regression analysis to analyze the data. The results showed that internal locus of control and self-efficacy have a positive and significant effect while external locus of control has a positive but not significant effect in the accounting section.   Keywords: Internal Locus of Control, External Locus of Control, Self Efficacy, and Understanding of Accounting